Spatiotemporal Variability of Temperature, Relative Humidity and Rainfall in Different Altitudes of Lower Lake Victoria Basin, Kenya - Olela, Samwel Odhiambo; Makokha, George L.; Obiero, Kennedy Obiero (Journal of Climate Policy, 2022)
Purpose: Global Climate Variability and Change are among environmental challenges with adverse consequences in the world. Their impacts include heightened temperatures, heightened or lowered rainfall and Relative Humidity. Those impacts depend on a place or how sensitive the people are. Examples of variations at the global scale which do influence local climate elements include: North Atlantic Oscillation (NOA), El Niño Southern Oscillation (ENSO), and Madden-Julian Oscillation. Lower Lake Victoria Basin (LLVB), Kenya was suspected to experience such variations differently due to varied altitudes. This study sought to investigate variability of selected climate elements in different altitudes of the LLVB, Kenya. Methodology: Meteorological data were obtained per county i.e. Migori - South Nyanza (SONY) Central Meteorological Station, Kisumu - Kisumu Airport Meteorological Station and Kakamega -Mumias Sugar Company (MSC) Meteorological Station. Data for the three selected climate parameters were collected for twenty years except Relative Humidity from Kisumu Airport which was available for only 12 years (2009-2020). ANOVA, Shapiro Wilk W test, Tukeys Honest Significance Difference (HSD) test, Time Series and Pearson's Correlation Coefficient were used for analysis. Findings: The findings showed that the elements significantly varied: Temperature F = 120.87, P = 0.0001; rainfall (F = 24.56, P = 0.000 and Relative Humidity (RH) F = 30.37, P = 0.0001. Temperature means correlated with altitudes revealed a negative correlation (r = - 0.896). Extreme events were observed in rainfall. Unique Contribution to Theory, Policy and Practices: Extreme events of rainfall, increasing trends of selected climate parameters were observed in the study area. These were evidence that climate change has already become an aspect of concern in the study area. Impacts of such extreme events should be investigated to help construct mitigative and adaptive strategies which should be implemented early enough to prevent unwanted outcomes, otherwise similar investigations should be conducted to establish situations elsewhere at different altitudes.